District heating in the Nordic countries – modelling development of present systems to 2050 - Goop, Joel (My University, 2012)
District heating constitutes a significant part of the total energy use in Sweden, Finland, and Denmark. In a transition to a more sustainable energy system, district heating can play an important role, e.g. through efficiency benefits and possibilities to utilise additional energy sources. In this project a computer-based cost-minimising investment model, describing the development of the production mixes of the national district heating systems in these countries from 2010 to 2050, is constructed using the TIMES model generator. The model is used for a comparative analysis of district heat production in three possible future scenarios, i.e. sets of consistent assumptions about the development in other parts of the energy system, e.g. the electricity supply system. The national district heating system in each country consists of hundreds of physically separate networks, all operating under different conditions. Modelling all these systems individually is, however, practically difficult, due to the time required for modelling and computation. Therefore a type system approach is used, where an entire class of actual systems, with similar production mixes and annual production volumes, is represented by one type system in the model. Based on a review of all networks described in the national district heating production statistics for each country, six type systems are constructed for Sweden and six for Finland, in total describing 85 % of the national annual district heat production in each country respectively. For Denmark, three type systems are constructed, describing 49 % of the national annual district heat production, and the remainder of the national production mix is described by an aggregation of the remaining actual systems. The constructed type systems are then described in the TIMES model. Three scenarios are studied. Two scenarios are designed to represent different pathways to reducing carbon dioxide emissions, one market-based approach with high carbon dioxide emission costs and one focusing on energy efficiency and support for renewable energy sources. The third scenario is a reference development, where current policies are extended into the future. Model results show that the cost-minimal development for the district heating systems in Finland and Denmark may include a transition from coal and natural gas to, primarily, biomass fuelled production facilities. If combined with a decreasing demand for district heat, this can lead to a substantial decrease in the electricity production from combined heat and power plants of up to 50 % in Denmark according to the model results. It can also be seen that a decreasing district heat demand in Sweden may, in the cost-minimal development, lead to difficulties in utilising the heat from waste incineration.
Keywords: Energi; Hållbar utveckling; Övrig annan teknik; Energy; Sustainable Development; Other Engineering and Technologies not elsewhere specified